Politeness strategies for maintaining english and vietnamese conversations (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
First of all, I would like to express my deepest and most sincere gratitude to Ms. Nguyen Thi My Phuong, my respected supervisor who has initiated the idea for the topic and granted to me her untiring and valuable assistance throughout the process of my writing. Her practical advice as well as useful suggestions and important feedback have encouraged me a lot to overcome my difficulties and pressures in doing the study and completed it. I am greatly indebted to my teachers at Da Nang Colleague of Foreign Language for their valuable lectures and wide knowledge, which guided my research work. This study could not be completed without a small group of American people whom I owe a debt of gratitude. I am also sincerely grateful to thank all of my colleagues in Ba Gia High School for their enthusiastic participation and their share partly of my work, without which this research could not become possible. Finally, I would further to take this opportunity to express my profound gratitude to my family, especially my mother, who has given me constant unfailing moral support and warm- hearted encouragement from the beginning to the end of my thesis.